ANALISIS KESEJAHTERAAN MASYARAKAT DI KABUPATEN/KOTA PROVINSI BALI SAAT PANDEMI COVID-19 - Susanto, Fabiani Vanda; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Regional development is expected to be able to overcome ongoing problems such as reducing poverty levels, unemployment rates, very low education and other inequalities between regencies/cities so as to improve people's living standards. This study uses panel data with time series data for 5 years from 2017-2021 and cross section data for 9 districts/cities in Bali Province so that the total observations are 45 observation points. The data used is secondary data with data collection methods, namely non-participant observation. The data collected was then analyzed using panel data regression analysis techniques and multiple linear regression analysis. The results showed that the pandemic had a negative and significant effect on people's welfare, the district minimum wage had a positive and significant effect on people's welfare, and unemployment had no effect on people's welfare in the Regency/City of Bali Province. Keywords: Pandemic, District Minimum Wage, Unemployment, Community Welfare